Rho and Rab Family Small GTPases in the Regulation of Membrane Polarity in Epithelial Cells - Ebnet, Klaus; Gerke, Volker (Frontiers in Cell and Developmental Biology, 2022)
Membrane polarity, defined as the asymmetric distribution of lipids and proteins in the plasma membrane, is a critical prerequisite for the development of multicellular tissues, such as epithelia and endothelia. Membrane polarity is regulated by polarized trafficking of membrane components to specific membrane domains and requires the presence of intramembrane diffusion barriers that prevent the intermixing of asymmetrically distributed membrane components. This intramembrane diffusion barrier is localized at the tight junctions (TJs) in these cells. Both the formation of cell-cell junctions and the polarized traffic of membrane proteins and lipids are regulated by Rho and Rab family small GTPases. In this review article, we will summarize the recent developments in the regulation of apico-basal membrane polarity by polarized membrane traffic and the formation of the intramembrane diffusion barrier in epithelial cells with a particular focus on the role of Rho and Rab family small GTPases.